Case Report: Protein-Losing Enteropathy in Association With Tuberculosis-Related Constrictive Pericarditis - Xi, Yue; Chen, Zhi; Hao, Kun; Liu, Xiaorong (Frontiers in Pediatrics, 2022)
Protein-losing enteropathy (PLE) is a clinical disorder in which an excessive amount of serum protein is lost into the gastrointestinal tract, resulting in hypoproteinemia and malnutrition. PLE is associated with a wide range of gastrointestinal disorders and the rare complication of constrictive pericarditis. We report a case in which pericardiectomy achieved marked improvement of extremely severe hypoalbuminemia caused by PLE associated with tuberculosis-related constrictive pericarditis. The formation of diarrhea and edema was aggravated by PLE, resulting in hypoalbuminemia. Cardiac computed tomography showed a calcified pericardium. Echocardiography showed decreased cardiac function underlying PLE. Functional imaging with technetium-99m serum albumin identified the region of protein leakage as the intestine. After pericardiectomy, the diarrhea ceased completely. Serum albumin concentrations were increased (3.3–3.7 g/dL), which indicated resolution of the PLE.